GEOLOGI DAN STUDI KONTROL STRUKTUR TERHADAP MINERALISASI DI DAERAH ARINEM, GARUT, JAWA BARAT: GEOLOGY AND STRUCTURAL CONTROL ON MINERALISATION OF THE ARINEM AREA, GARUT, WEST JAVA - Rudyawan, Alfend; Sujatmoko, Muhammad Lugas; Rizal, Yan (Buletin Sumber Daya Geologi, 2025)
Exploration by PT Aneka Tambang in 1981 identified several promising mineral prospects in West Java, categorized as low- to high-sulfidation epithermal types. One such prospect is the Arinem area in Garut, which became the focus of this study. Spanning 0.46 km², this area is located 45 km from Garut city. The data used in this research include field data and core samples from seven boreholes provided by PT ANTAM Tbk. This study aims to understand the geological and hydrothermal alteration processes of the region using field work measurements, petrographic, mineralographic, and ASD specTERRA The study area consists of volcanic and volcaniclastic units, intruded by Pyroxene Andesite and Hornblende Andesite, with prominent hydrothermal alteration zones. The geological structures include the Left-Lateral Arinem Fault and the Right-Normal Arinem Fault, both of which control hydrothermal processes. Minerals such as pyrite, chalcopyrite, galena, and sphalerite were identified, with mineral veins trending north – south. The results suggest that Arinem is a part of an en-echelon structure arrays part of a larger left lateral strike slip system in West Java that cross-cut by the younger NE – SW dextral faults. This provides crucial insight into the geology, subsurface alteration and mineralization distribution, highlighting its significance for ongoing exploration efforts.